Size and frequency of natural forest disturbances and the Amazon forest carbon balance - Espírito-Santo, Fernando D.B.; Gloor, Manuel; Keller, Michael; Malhi, Yadvinder; Saatchi, Sassan; Nelson, Bruce; Oliveira, Raimundo C., Junior; Pereira, Cleuton; Lloyd, Jon; Frolking, Steve; Palace, Michael; Shimabukuro, Yosio E.; et al. (Nature Publishing Group, 2014)
Forest inventory studies in the Amazon indicate a large terrestrial carbon sink. However, field plots may fail to represent forest mortality processes at landscape-scales of tropical forests. Here we characterize the frequency distribution of disturbance events in natural forests from 0.01 ha to 2,651 ha size throughout Amazonia using a novel combination of forest inventory, airborne lidar and satellite remote sensing data. We find that small-scale mortality events are responsible for aboveground biomass losses of ~1.28 Pg Cy-1 over the entire Amazon region. We also find that intermediate-scale disturbances account for losses of ~0.01 Pg Cy-1, and that the largest-scale disturbances as a result of blow-downs only account for losses of ~0.003 Pg Cy-1. Simulation of growth and mortality indicates that even when all carbon losses from intermediate and large-scale disturbances are considered, these are outweighed by the net biomass accumulation by tree growth, supporting the inference of an Amazon carbon sink.